Determination of economic injury level of mustard aphid (Lipaphis erysimi) on mustard - Sherwani, Asma; Mukhtar, Malik (Indian Journal of Plant Protection, 2026)
The Mustard is one of the important crops of rabi season in Kashmir. It provides forage to honey bees in early spring besides oilseed for human consumption. Mustard crop is attacked by various insect pests out of which Mustard aphid (Lipaphis erysimi Kalt.) occupies a predominant position. It thrives well under climatic conditions of Kashmir and both nymphs and adults remain in a damaging stage from late winter to early spring when the crop is at flowering and pod formation stages leading to various deformities in the plant. Management is often restricted to insecticides that are applied indiscriminately without any regard to threshold levels. In this study an experiment was conducted to establish the economic threshold level of mustard aphid in the rabi season of 2023-2024. The crop was subjected to five exposure periods based on the incidence of the pest in the various fields of mustard over the period of years. The findings revealed that economic injury level (EIL) of mustard aphid was worked out to be 72.19 aphids/10 cm apical twig/plant, while as economic threshold level (ETL) was found to be 54.14 aphids/10cm apical twig/plant. There was a strong negative correlation (r= 0.99) between aphid density and seed yield of mustard.